Numerical study of hypersonic surface heat flux with different air species models. (April 2020) - Zhao, Yipu; Huang, Haiming
Abstract: The chemical nonequilibrium mathematical model is built to investigate the effect of the air species model on the heat flux, based on Navier-Stokes equations, the Gupta chemical kinetics model and air species models, including the five-species model, the seven-species model and the eleven-species model. The code is programmed in FORTRAN, and verified by making a comparison with the data in the literature. A good deal of calculations under different cases are completed to obtain differences among three air species models by taking the heat flux as an example. Results demonstrate that the heat flux computed by the seven-species model is largest among three air species models, meanwhile, the difference of the heat flux enlarges with the enhance of Mach number, which proves the necessity of using the seven-species model at higher Mach number. Highlights: The effect of air species models on the heat flux is obtained. The heat flux computed by the seven-species model is largest among three models. The difference of the heat flux is caused by the surface catalysis in three models. The difference of the heat flux enlarges with increases of Mach number.